Penyebab Kekerasan Dalam Rumah Tangga (KDRT) di Kecamatan Bantul Kabupaten Bantul Yogyakarta - Maria Yeny Eskawati; Yulian Endarto (VISIKES: Jurnal Kesehatan Masyarakat, 2017)
Increasing Gender Equality and Women’s Empowerment is one of the Millennium Development Goals (MDGs) goals that is continued in Sustainable Development Goals (SDGs). However, domestic violence has increased signiicantly every year. The domestic violance in Indonesia, 2010 reached 295 836 cases and in Bantul District increased from 6 to 12. This study aims to determine factors that lead to domestic violence in Bantul Sub-District.This was descriptive qualitative study, with purposive sampling techniques. In the beginning of the study, there were about two dozen informants, but only four people who were willing to become informants. Data was collected through in-depth interviews, semi standard way and reseracher as a key instrument. The source triangulation was used for data validation.There were many factors that lead to domestic violences: the economic situations, harmony in intimate relationships, conidence, communication, stress, and the past experiences. The education was not a cause of domestic violence.Key words: domestic violence